Sastra Sebagai Cermin Kehidupan dalam Cerpen “Gede Ombak Gede Angin”: Analisis Nilai Pendidikan Bahasa Dan Sastra Agama Hindu - Dewik, Ni Putu Besanda; Dewi, Ni Luh PT. Putriyani; Restiti, Ni Komang; Wahyuni, Gusti Ayu Hari (Dharma Sastra : Jurnal Penelitian Bahasa dan Sastra Daerah, 2025)
reflects the social and spiritual realities of contemporary Balinese society. This study aims to reveal the values of Hindu religious language and literature education contained within the story through content analysis and semiotic approaches. The results show that the narrative highlights deviations from dharma values, particularly within family life, as well as the karmic consequences of deviant behaviors such as gambling addiction through cockfighting. The principles of dharma, karma phala, and mokṣa are strongly reflected in the protagonist’s inner journey. Symbolic analysis of story elements, such as the rotten cassava and children's tears, enriches the spiritual meaning of the narrative. This study emphasizes that regional literary works like Gede Ombak Gede Angin have great potential as media for character education based on Hindu teachings. The findings encourage the use of local literature in fostering moral education for the younger generation amidst the challenges of globalization